COGNITIVE DYSFUNCTION AMONG PATIENTS UNDERGOING SURGERY WITH GENERAL AND REGIONAL ANAESTHESIA - Kaliamoorthy, Charanya; K, Krishnamurthy; Shanmugavinayagam, Arumuganathan; Mukherjee, Moushumi Purkayastha; Kumar, Saravana (International Journal of Psychosocial Rehabilitation, 2020)
Postoperative cognitive changes have been reported for over a century, and anaesthesia has often been mentioned as a possible cause of this problem. The study aimed to assess cognitive dysfunction among patients receiving anaesthesia. 26 patients undergoing surgery with general anesthesia and 26 patients undergoing surgery with regional anesthesia were recruited. Informed consent and socio-demographic details were obtained and their cognitive functions were assessed using SMMSE, DSST, TMT-A, and BCRS. The tests were done two days before surgery, on postoperative day one and postoperative day three in patients undergoing surgery with general and regional anesthesia. The results concluded that both general and regional anesthesia affects cognition of the individual but the rate of cognitive dysfunction was significantly higher in patients who underwent surgery with general anesthesia when compared to regional anesthesia. Further cognitive dysfunction was more postoperatively than before surgery which confirms the fact that postoperative cognitive problems are common in patients following major surgeries.